Bacteriophage T4 DNA polymerase mutations that confer sensitivity to the PPi analog phosphonoacetic acid. - Reha-Krantz, L J (1993)
Mutations that conferred sensitivity to the pyrophosphate analog phosphonoacetic acid in bacteriophage T4 DNA polymerase were identified. The mutations were loosely clustered in four regions of the gene. As found for herpes simplex virus DNA polymerase, T4 mutations that altered sensitivity to phosphonoacetic acid also altered sensitivity to nucleotide analogs. Some of the T4 DNA polymerase mutations also altered the ability of the enzyme to translocate from one template position to the next and affected DNA replication fidelity. Kornberg (A. Kornberg, Science 163:1410-1418, 1969) envisioned a DNA polymerase active center which accommodates primer terminus and template DNAs and the incoming nucleotide. Some mutations identified on the basis of sensitivity to phosphonoacetic acid may be part of such an active center because single amino acid substitutions simultaneously alter several DNA polymerase functions.